A rare case report of acute upper gastrointestinal hemorrhage due to splenic artery pseudoaneurysm. (December 2021) - Dinh Luan, Nguyen; Duc, Nguyen Minh; Hong Son, Nguyen; Minh Hien, Tran; Anh Huy, Le; Tan Tai, Nguyen; Tran Kinh, Bui; Minh Loi, Hoang
Splenic artery aneurysm and splenic artery pseudoaneurysm are rare vascular pathologies. The splenic artery represents the third most common site for intra-abdominal aneurysms. In contrast with true splenic artery aneurysm, splenic artery pseudoaneurysm is typically symptomatic, presenting with a range of symptoms, from abdominal pain to hemodynamic instability due to rupture. However, gastrointestinal hemorrhage is an uncommon complication of splenic artery pseudoaneurysm. We report a case of acute upper gastrointestinal hemorrhage due to splenic artery pseudoaneurysm rupture. The patient was successfully treated by endovascular intervention.